2020
DOI: 10.1016/j.toxrep.2020.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the ameliorative effect of oleic acid in rejuvenating phenylhydrazine induced oxidative stress mediated morpho-functionally dismantled erythrocytes

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…Many illnesses, including hematological abnormalities, have oxidative stress as a major contributing factor in their origin, as is well known [35]. Hemolytic anaemia is caused by a variety of harmful cellular processes, including membrane lipid peroxidation and protein oxidation, which erode the integrity of RBC membranes and are caused by the autoxidation of PHZ [36].…”
Section: Discussionmentioning
confidence: 99%
“…Many illnesses, including hematological abnormalities, have oxidative stress as a major contributing factor in their origin, as is well known [35]. Hemolytic anaemia is caused by a variety of harmful cellular processes, including membrane lipid peroxidation and protein oxidation, which erode the integrity of RBC membranes and are caused by the autoxidation of PHZ [36].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Berköz et al ( 2021 ) confirmed the capacity of OLE to decrease lipid peroxide in the RBC membrane, which reduces hemolysis and prolongs their life span. Moreover, Banerjee et al ( 2020 ) verified the high efficiency of oleic acid, a major component of OLE based on GC–MS analysis, in safeguarding the morphology, intracellular antioxidant status, and the metabolic enzyme activities of erythrocytes via its antioxidant mechanisms. Furthermore, the higher amount of bioactive compounds like phytol in both OLE and MLE, with their high antioxidant capacity, could be responsible for counteracting PTL-induced normocytic normochromic anemia (P Costa et al 2016 ; Santos et al 2013 ; Usman et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…These ROS can cause oxidative damage to cellular macromolecules such as lipids, proteins, and DNA, leading to cellular dysfunction and damage [40,41]. PHZ-induced oxidative stress can also lead to the depletion of endogenous antioxidant enzymes which are involved in scavenging ROS [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…PHZ triggers the production of excessive ROS, disrupting the balance between oxidation and antioxidant defence. This imbalance results in lipid peroxidation (LPO) and eventual oxidative harm to proteins and DNA [42,43]. MDA is the main result of the peroxidation of polyunsaturated fatty acids, and its presence indicates the level of injury in cells or tissues.…”
Section: Effect On Oxidative Stress Parametersmentioning
confidence: 99%